The effects of smoking on cardiac structure and function in a general population. (3rd October 2022) - Holt, E; Skaarup, K G; Lassen, M C H; Johansen, N D; Joergensen, P G; Hauser, R; Lind, J N; Jensen, G; Schnor, P; Prescott, E; Soegaard, P; Moegelvang, R; et al.
Abstract: Background: Cigarette smoking is the leading preventable cause of death worldwide. Smoking is known to cause coronary artery disease, but studies have also shown that smoking independently is associated with higher risk of heart failure. However, the link between smoking and cardiac structure and function is not yet fully examined. Purpose: The aim of the study was to investigate the independent effect of cigarette smoking on cardiac structure and function in a general population using echocardiographic measures. Methods: A prospective cohort of 3, 874 participants from a general population free of prevalent heart disease underwent an echocardiographic examination including two-dimensional speckle-tracking analysis. Smoking history was obtained through a self-administered questionnaire, that generated three groups; current smokers (18.6%), former smokers (40.9%) and never smokers (40.5%). Pack-years were estimated from the questionnaire. Results: After multivariable adjustment for age, sex, body mass index, hypertension, hypercholesterolemia, diabetes and lung function, current smokers had significantly alterations in septal thickness (1.1±0.2 cm, P=0.018) and relative wall thickness (0.4±0.1 cm, P=0.016) compared to never smokers. Furthermore, left ventricular mass index (LVMi) was increased in current smokers compared to never smokers (85.8±19.3 g/cm 2, P=0.048). Reduced left ventricle systolic function as assessed by global longitudinal strain (GLS) was evident in current smokers compared to never smokers (19.1±2.3%, P<0.001). Additionally, after multivariable adjustment increasing pack-years was associated with decreases in left ventricular ejection fraction (LVEF) (β=−0.04, P=0.031), E/A ratio (β=−0.06, P<0.001) and GLS (β=−0.04, P=0.008). Comparing cardiac structure and function in never smokers, continuous smokers and former smokers after 10 years, showed that continuous smokers developed increased LVMi (Δ=3.97±17.48 g/cm 2, P<0.001) and decreased GLS (Δ=−0.77±3.84%, P=0.04) and LVEF (Δ=−4.23±5.7, P<0.001) compared to never and former smokers. Conclusion: In a large general population study without known heart disease, current smoking and accumulated pack-years were independently associated with alterations in cardiac structure and reduced systolic function. Furthermore, we found that continuous smokers over a 10-year period developed relatively worse systolic function and increased LV structure alterations compared to never smokers and to participants that stopped smoking during that period. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Copenhagen City Heart Study is funded by The Danish Heart Foundation andThe Metropolitan Region of Denmark.